Pulmonary light chain deposition disease secondary to Sjögren disease: a case report - Xu, Xiaotong; Wang, Lingjian; Zhou, Chunsheng; Zhang, Lu; Zhang, Ting; Peng, Min; Feng, Rui’e; Shi, Juhong (Frontiers in Immunology, 2026)
Pulmonary light chain deposition disease (PLCDD) is a rare disorder characterized by the deposition of immunoglobulin light chains in the lungs, often associated with lymphoplasmacytic proliferative and autoimmune disease such as primary Sjögren disease (pSjD). Due to its rarity, there is currently no established definitive management of PLCDD. In this case report, we present the clinical presentation of a 42-year-old female with a history of pSjD who experienced recurrent hemoptysis over a period of 3 years. Radiological and pathological assessments confirmed pulmonary involvement of light chain deposition disease. Despite initial failure of glucocorticoids and immunosuppressive agents in targeting pSjD, subsequent combination therapy with bortezomib and dexamethasone (BD) resulting in significant clinical and radiological improvement. The successful use of this combination treatment in PLCDD represents a significant breakthrough, highlighting the potential effectiveness of targeted therapies for PLCDD secondary to autoimmune disease.